Shelf-life extension of herring (Clupea harengus) using in-package atmospheric plasma technology. (May 2019) - Albertos, I.; Martin-Diana, A.B.; Cullen, P.J.; Tiwari, B.K.; Ojha, K. Shikha; Bourke, P.; Rico, D.
Abstract: Atmospheric cold plasma is a green and emerging technology, highly interesting to the food industry for its application. Dielectric Barrier Discharges (DBD) can generate atmospheric cold plasma inside sealed packages filled with air through the use of high voltages. This study investigated the use of a large gap DBD design to generate a plasma discharge within the headspace of packaged herring fillets, and its effects on microbiological and quality markers of the fish stored for 11 days at 4 °C. DBD plasma treatment conditions were 70 kV or 80 kV for 5 min treatment time. Results showed that the microbial load (total aerobic mesophilic, total aerobic psychrotrophics, Pseudomonas, lactic acid bacteria and Enterobacteriaceae ) were significantly (p < 0.05) lower in the treated samples compared to the control samples. However, samples exposed to the lowest applied voltage better retained key quality factors (lower oxidation and less colour modification). DBD-treatment caused a reduction in trapped water in the myofibrillar network (T21), identified using low-field nuclear magnetic resonance of protons ( 1 H LF NMR). The results indicate that in-package plasma treatment could be employed as an effective treatment for reducing spoilage bacteria in fish. Industrial relevance: Dielectric Barrier Discharge (DBD) was evaluated as a treatment for highly perishable fish products. DBD's is a safety and lower costs alternative for processing industry. DBD has been scarcely tested on fish; this work showed results on quality and shelf-life of a highly perishable fish species, which might serve as reference for processing optimisation of fish products minimally processed by DBD. Highlights: DBD reduced spoilage during storage in fresh herring. DBD does not produce harmful chemical residues. DBD is an eco-friendly technology to increase fresh fish shelflife.